Breast cancer metastasis to bone: From epithelial to mesenchymal transition to breast osteoblast-like cells. (July 2021) - Scimeca, Manuel; Trivigno, Donata; Bonfiglio, Rita; Ciuffa, Sara; Urbano, Nicoletta; Schillaci, Orazio; Bonanno, Elena
Abstract: In this review we highlighted the newest aspects concerning the physiopathology of breast cancer metastatization into the bone including: a) in situ biomarkers of breast cancer metastatic diseases, b) biological processes related to the origin of metastatic cells (epithelial to mesenchymal transition), c) the nature and the possible role of Breast Osteoblast-Like Cells in the formation of bone lesions and d) the prognostic value of breast microcalcifications for the bone metastatic disease. In addition, the more recent data about the biology of breast cancer metastatic process and the origin and function of Breast Osteoblast-Like Cells have been analyzed to propose the use of molecular imaging investigations able to identify early neoplastic lesions with high propensity to form bone metastasis in vivo .